TRADEMARK REGISTRATION FOR MSMES - Nicky Winata; Winsherly Tan (ConCEPt - Conference on Community Engagement Project, 2022)
MSMEs are one of the things that encourage the development of the economy in Indonesia so that the government also helps in its development to make it easier for MSMEs to develop their businesses, so the government has also issued several policies that make it easier for MSMEs, such as the requirements for their formation and also related with trademark registration for MSMEs, the costs required are also reduced. The author's partners want to expand their business so that they want to expand their business with a Franchise or Franchise business model, the method used in solving problems is starting from educating partners related to several things that need to be known related What is IPR and in the registration, a note is made on the documents that are needed to be used as a necessary requirement for registering the required trademark IPR, the Condition of the Partner after Implementation is Partners understand more about how to register online trademarks and the documents that need to be prepared related to online trademark registration, especially for SMEs, and until this article was made the registered mark is still in the announcement stage and has not yet received a registered trademark certificate.